FILSAFAT POLITIK KAUTILYA DALAM ARTHASASTRA - N Nyoman Yoga Segara (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2013)
AbstractArthasastra is one of Upaweda parts. It reveals some aspects such as the politics, government, leadership, economics, justice, and administration. Kautilya who is the author is considered successfully to devote his political idea and make it as the book that can be used to reach the spiritual and material happiness. Those are expressed by Chandragupta who is prepared to be the leader and successor of Mauriya dynasty. Kautilya’s idea in Arthasastra is Hindu political philosophy that is still alive until this day.Keywords: Arthasastra, Kautilya, political philosophy